Optimalisasi Bonus Demografi Terhadap Indikator Makroekonomi (Studi Empiris di Provinsi Bali Periode 2010-2017): Optimalisasi Bonus Demografi Terhadap Indikator Makroekonomi (Studi Empiris di Provinsi Bali Periode 2010-2017) - Baghas Budi Wicaksono (Universitas Pasundan, 2022)
Bali has economic potential and experiences a demographic bonus earlier with a duration longer than the national one. However, the requirements for utilizing the demographic’s bonuses as an engine of economic growth do not carry out optimally. This condition is due to the unpreparedness of the community to provide skilled, educated, and technologically skilled workers. Though Human investment is long-term, the bonus demographics are not yet ready to be optimized. This research model uses multiple linear regression analysis with four independent variables, population growth rate, number of unemployed, dependency ratio, and Gini Ratio. The regression results show that all independent variables are related to the hypothesis. The relationship and level of significance concluded that the demographic transition in Bali provided a bonus for economic growth in the region.